Information- Seeking Behavior and Utilization among Snail Farmers in Oyo State, Nigeria: Implications for Sustainable Animal Production - E. O. Owolade; Arimi Kayode (Journal of International Agricultural and Extension Education, 2012)
The authors of this study examined the information-seeking behavior and utilization among snail farmers in Oyo State with the view of improving animal production to achieve food and nutritional security.Simple random sampling was used to select one hundred and twenty respondents out ofthree hundred and sixty-five registered members in Oyo state. Interview schedule was administered to elicit information relating to socio-economic characteristics, information-seeking behaviour and utilization among snail farmers and the constraints faced by the snail farmers. Data were analyzed using frequency counts, mean, percentages, and correlation. Most of the respondents were literates. This factor increased their capacities for seeking and utilizing agricultural information. Lack of credit facilities and inadequate information from extension agents were the major constraints identified by the farmers. There was a significant relationship between the sources of information and information-seeking behavior of these farmers as well as the utilization of such information (r = -0.261; pv = >0.05). Significant relationship also existed between constraints faced by the farmers and information-seeking behavior and utilization by these farmers (r = -0.23, pv = 0.01). Most of the respondents had high information-seeking behavior and utilization, which impliesthat farmers are willing to seek information that will improve their productivity.Efforts should therefore be made to promote the information utilization of farmers through the extension services of agricultural development projects in order to facilitate the transfer of technology. This will enhance the productivity and income of snail farmers and subsequently improve their standard of living.
Keywords: Information-Seeking Behavior; Utilization; Technology; Production; Snail Farmers; Nigeria